Correction to the misapplication of the name Tectaria subsageniacea (Tectariaceae) in China - Dong, Shi-Yong (Phytotaxa, 2017)
The misapplication of the name Tectaria subsageniacea or Ctenitopsis subsageniacea, is corrected here. The nomenclature type of these names is an individual of T. fuscipes and the plants which have long been referred to as C. subsageniacea or T. subsageniacea in China should be named T. austrosinensis. A lectotype is designated for T. austrosinensis.